Exploring the Asthma - Obesity Link Using Advanced Imaging Techniques - Krivošová, Michaela; Barošová, Romana; Lukáčová, Eva; Hanusrichterová, Juliana; Němcová, Nikolett; Kolomazník, Maroš; Mokrý, Juraj; Mokrá, Daniela (Physiological research, 2025)
The global rise in obesity has emerged as a significant health concern, amplifying susceptibility to various diseases, including asthma. Epidemiological evidence demonstrates a higher prevalence of asthma among obese individuals, with obesity exacerbating asthma severity and control. This review aims to explore the interplay between asthma and obesity assessed by objective imaging methods and discusses the consistency between anthropometric and imaging methods. A literature search was conducted with the main keywords "asthma", "obesity", and "imaging techniques" using databases such as PubMed, Web of Sciences, and Scopus for the relevant articles published up to January 2024. The consistency between Body Mass Index (BMI), Waist Circumference (WC), and results from imaging techniques is uncertain. Unlike anthropometric methods, imaging methods provide us with the exact location of adipose tissue as well as fat and lean mass distinction, which can be further correlated with different airway parameters and respiratory system functions and dysfunctions. Studies indicate that the relationship between lung functions and obesity is more complex in females. Abdominal visceral fat is supposed to be the major asthma predictor already in the pediatric population. The connection between obesity and asthma is already evident in children and adolescents. Imaging methods can measure visceral and subcutaneous fat mass and both contribute to the association between obesity and lung functions. These methods are more accurate and reproducible but require more time and expertise. Key words Asthma, Obesity, Magnetic resonance imaging, Dual-energy, X-ray absorptiometry, Bioimpedance analysis.
Keywords: obezita; Obesity; bronchiální astma; magnetická rezonanční tomografie; Body Mass Index; lidé; index tělesné hmotnosti; Magnetic Resonance Imaging; Humans; Asthma